Інформатизація та месенджери - Андрєєва, А. Ю. (ХНУРЕ, 2020)
The article gives the analysis of the specificity of modern communicative open space and the tendency of his development is considered. It is accented on factors that promote development of tendencies to globalization and unification of information open space. Some positive and negative consequences of the given process, their influence on development of communication technologies are opened.
Keywords: філософія; інформатизація та месенджери